Photonic potential for TM waves - Alberucci, Alessandro; Jisha, Chandroth P.; Nolte, Stefan (Optics Letters, 2018)
We discuss the effective photonic potential for TM waves in inhomogeneous isotropic media. The model provides an easy and intuitive comprehension of form birefringence, paving the way for a new approach on the design of graded-index optical waveguides on nanometric scales. We investigate the application to nanophotonic devices, including integrated nanoscale wave plates and slot waveguides.
CRIS-Team Scopus Importer:2023-04-20